2022
DOI: 10.7759/cureus.30662
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of COVID-19 in Adult Males With Hemophilia A: A Propensity Score-Matched Analysis

Abstract: BackgroundHypercoagulability is a major pathologic event in COVID-19. Factor VIII plays an important role in hemostasis, and high levels of factor VIII have been shown to be associated with an increased risk of thrombosis and severe disease. Little is known about the impact of COVID-19 on clinical outcomes in patients with hemophilia A. MethodologyRetrospective data of adult male patients with COVID-19 with and without hemophilia A were retrieved from the TriNetX database (Cambridge, USA). The 1:1 propensity s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
1
0
Order By: Relevance
“…A retrospective study in hemophilia A patients reported that COVID-19 is linked to a higher risk of bleeding and hospitalizations [31] due to the possible development of FVIII inhibitors after an immune trigger [20].…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective study in hemophilia A patients reported that COVID-19 is linked to a higher risk of bleeding and hospitalizations [31] due to the possible development of FVIII inhibitors after an immune trigger [20].…”
Section: Discussionmentioning
confidence: 99%
“…Since COVID-19 is associated with coagulation and thrombotic disorders, little was known about the infection's impact on the clinical outcomes of patients with hemophilia. A retrospective study by Mericliler et Narayan with 1758 adult male patients reported that COVID-19 did not increase the mortality of COVID-19 in hemophilia A patients but increased the risk of bleeding and hospitalizations [35].…”
Section: Inherited Blood Coagulation Disorders and Covid-19 Vaccinesmentioning
confidence: 98%